Hubungan Pola Asuh Ibu Dengan Keberhasilan Toilet Training Pada Anak Usia Prasekolah (4-6 Tahun) Di Raudhatul Athfal Al-Mu’minin Kabupaten Ciamis - Lusi Lestari; Ima Sukmawati; Devi Amanda (LPPM STIKes Muhammadiyah Ciamis, 2018)
Toilet training in children is an attempt to train children so that the children were able to control in the conduct of urination and defecation. Do urinate and defecate, children need good preparation physically, psychologically or intellectually, through the preparation of the expected child able to control bowel movements and urination with independently. Factors that can affect the success of toilet training is parenting the mother or parents. A survey in the United Kingdom, was a half million children aged 6-16 years still love bed wetting, about 17% of children aged five years, 14% of children aged seven years, 9% of children aged nine years old, and 1-2% of the children aged 15 years still bedwetting. As for the cases of bedwetting in children 6 years of age in Indonesia is around 12%. This study aims to determine the relationship between mother's parenting with successful toilet training in preschoolers (4-6 years) in Raudhatul Athfal Al-Mu'minin District Ciamis. This type of research is quantitative with cross sectional study design. Total population 82 people and sampling by way of purposive sampling. Bivariate analysis using Chi Square test. The results showed that as many as 63 respondents (100%) that implementing democratic parenting all succeed in toilet training, as much as 2 respondents (100%) that implements the authoritarian parenting all haven't managed to do the toilet training and as many as 3 of the respondents (100%) that implements the permissive parenting all have not succeeded in toilet training. The result of statistical test, p value = 0.000 <(? = 0,05) means that there is a significant correlation between mother care pattern with successful toilet training in preschool age children (4-6 years). Conclusion of this study is that there is a significant relationship between mother care pattern with successful toilet training in preschool children (4-6 years) in Raudhatul Athfal Al-Mu'minin District Ciamis. It is expected that mothers can apply democratic parenting so that successful toilet training can be achieved.